Genomic driven factors enhance biocatalyst-related cellulolysis potential in anaerobic digestion. (August 2021) - Zhuang, Huichuan; Lee, Po-Heng; Wu, Zhuoying; Jing, Houde; Guan, Jianyu; Tang, Xiaojing; Tan, Giin-Yu Amy; Leu, Shao-Yuan
Graphical abstract: Highlights: Genomic information of cellulosome-embedded prokaryotes in ADs were commented. Substrate-related factors of lignocellulosic biomass in ADs were introduced. Cellulosome related subunits were overviewed with corresponding genes. Cellulose separation methods to enhance cellulosome cellulolysis were studied. Benefits and mechanisms of micro-aeration and enzyme additions were reported. Abstract: Anaerobic digestion (AD) is a promising technology to recover bioenergy from biodegradable biomass, including cellulosic wastes. Through a few fractionation/separation techniques, cellulose has demonstrated its potential in AD, but the performance of the process is rather substrate-specific, as cellulolysis bacteria are sensitive to the enzyme-substrate interactions. Cellulosome is a self-assembled enzyme complex with many functionalized modules in the bacteria which has been gradually studied, however the genomic fingerprints of the culture-specific cellulosome in AD are relatively unclear especially under processing conditions. To clarify the key factors affecting the cellulosome induced cellulolysis, this review summarized the most recent publications of AD regarding the fates of cellulose, sources and functional genes of cellulosome, and omics methods for functional analyses. Different processes for organic treatment including applying food grinds in sewer, biomass valorization, cellulose fractionation, microaeration, and enzymatic hydrolysis enhanced fermentation, were highlighted to support the sustainable development of AD technology.